The Validity of HOTS Assessment Instrument to Measure Ability of Problem-Solving on Thermochemistry Materials - Inayati, Ismi; Susilaningsih, Endang; Jumaeri, Jumaeri (International Journal of Active Learning, 2022)
This research is motivated by the lack of variety of HOTS questions to measure ability of problem-solving on thermochemistry materials. The objective of this research is to develop a HOTS assessment instrument to measure valid problem-solving abilities on thermochemical materials. The research method used is RD with a 4D model adapted from Thiagarajan that is converted into 3D, that are define, design, and develope. The subjects of this research were 77 students of class XI MIPA SMA Negeri 1 Pemalang. The data collection sources and methods include: interviews, questionnaires, and tests. The analysis results of the content validity of the instrument obtained that the Aiken'S coefficient in all aspects measured was above 0.75. This shows that the HOTS assessment instrument is very valid. The validity of the construct is seen from the value raw variance explained by measures 48.6% has very good criteria so that the question items are valid. The analysis results of the quality of the HOTS questions to measure problem-solving abilities are seen in terms of the validity of the items, it is known that there are 16 items that are said to be valid and 4 items are said to be invalid because they do not meet the requirements outfit MNSQ, Outfit ZSTD, and Point Measure Correlation.